2015
DOI: 10.2298/mpns1506187p
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections in patients with liver cirrhosis

Abstract: Bacterial infections are often found in patients with liver cirrhosis, the most frequent being pneumonia, urinary tract infection and spontaneous bacterial peritonitis. Gram negative bacteria, especially Escherichia coli were predominant in the etiology. The extent to which bacterial infections are taken into consideration in cases with liver cirrhosis is rather high; however, they are not proved etiologically to the satisfactory level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…[4] Although pneumonia exhibits higher mortality in patients with cirrhosis, majority of the studies focused on bacterial pneumonia as the most common cause of pneumonia in cirrhotic patients; other pathogens especially are usually underestimated in such patients and are often not underreported. [5,6] There are very few studies which have shown the influence of respiratory viruses (RVs) in clinical outcome of cirrhotic patients in CCU. [7][8][9] Till now, there is no published study showing the prevalence of RVs and their bacterial coinfections in cirrhotic patients admitted in CCU care.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Although pneumonia exhibits higher mortality in patients with cirrhosis, majority of the studies focused on bacterial pneumonia as the most common cause of pneumonia in cirrhotic patients; other pathogens especially are usually underestimated in such patients and are often not underreported. [5,6] There are very few studies which have shown the influence of respiratory viruses (RVs) in clinical outcome of cirrhotic patients in CCU. [7][8][9] Till now, there is no published study showing the prevalence of RVs and their bacterial coinfections in cirrhotic patients admitted in CCU care.…”
Section: Introductionmentioning
confidence: 99%
“…With a compromised immune system, patients with liver cirrhosis are more susceptible to a bacterial infection such as pneumonia, urinary tract infections, and spontaneous bacterial peritonitis (SBP) which can lead to significant morbidity and mortality [1,2]. Spontaneous bacterial empyema (SBEM) is often lessrecognized, which occurs in 2% of cirrhotic patients without hydrothorax and up to 13% of cirrhotic patients with hydrothorax [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the frequencies of technique failure and infection, such as peritonitis and ESI, were not different between patients with PD with and without LC. Infection, including peritonitis, is a serious complication in patients with LC, who are vulnerable to bacterial infections, which are directly related to sepsis and death (22,23). Therefore, patients with LC tend to discontinue PD more quickly than do non-LC patients once infection occurs in real clinical situations (24).…”
Section: Discussionmentioning
confidence: 99%